THE ABUNDANCE AND DIVERSITY OF MEGAGASTROPODA IN SEAGRASS BED ECOSYSTEM IN THE WATERS OF TIHI-TIHI VILLAGE, BONTANG CITY, EAST KALIMANTAN - Rahmasari, Dewi; irawan, aditya_irawan; Sari, Lily Inderia (Jurnal Perikanan Unram, 2025)
Seagrass beds provide habitat for the abundance and diversity of megagastropods that form the food chain in supporting the productivity of coastal waters. The purpose of this study was to determine the diversity and abundance of megagastropoda in the seagrass beds of Tihi-Tihi Village. This study was conducted in October 2024 - February 2025 using a purposive sampling method. Megagastropoda sampling using Van Veen Grab and seagrass stands using 50x50cm square frames. Data analysis included abundance, community structure index and morphometrics of individual megagastropoda, and seagrass stand density and Pearson Product Moment correlation analysis. The results of the study found 18 species of megagastropoda. Diversity in moderate criteria, moderate population uniformity and dominance in moderate criteria with an abundance of individuals reaching 567 individuals/m2. The seagrass found 4 species of seagrass, namely E. acoroides, T. hemprichii, C. rotundata, and H. ovalis. There is a positive and very close correlation between the abundance of megagastropoda and the characteristics of seagrass density.